2018
DOI: 10.1155/2018/9216578
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Hydraulic Properties of Granular Sandstone and Mudstone Mixtures

Abstract: The caved zone during longwall mining has high permeability, resulting in a mass of groundwater storage which causes a threat of groundwater inrush hazard to the safe mining. To investigate the hazard mechanism of granular sandstone and mudstone mixture (SMM) in caved zone, this paper presents an experimental study on the effect of sandstone particle (SP) and mudstone particle (MP) weight ratio on the non-Darcy hydraulic properties evolution. A self-designed granular rock seepage experimental equipment has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Hence, conventional methods cannot effectively drain gas from those seams [1]. e parameters of permeability and porosity play an important role in the study of accumulation and development of coalbed methane [2][3][4]. To increase the permeability of those coal seams, underground hydraulic fracturing technology to transform the seam structure is an effective way to achieve this goal [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, conventional methods cannot effectively drain gas from those seams [1]. e parameters of permeability and porosity play an important role in the study of accumulation and development of coalbed methane [2][3][4]. To increase the permeability of those coal seams, underground hydraulic fracturing technology to transform the seam structure is an effective way to achieve this goal [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…By comparing (13) and (16) The left-hand term of (82) is the counterforce of coal seam in the elastic zone on the left side of = 4 that is applied on the rock beam, while the right-hand term is the counterforce of coal seam in the hardened zone on the right side of = 4 that is applied on the rock beam. Equation (82) clarifies the issue in the calculation that the continuity of the counterforce of the coal seam at the junction between the elastic and hardened zones on the rock beam after the introduction of the hardened zone of coal seam.…”
Section: Methods To Determine the Maximum Support Pressurementioning
confidence: 99%
“…For instance, as the hanging roof distance increases, the overall load above the coal seam increases, and the maximum support pressure increases (Figure 2), but the residual strength of coal seam at coal wall m (i.e., the depth of softened zone remains constant, − 3 =8 m), c3 =8.6, 8.3, 8 m, c4 =2 m, the elastic modulus of roof is =25 GPa, the elastic foundation constant =0.4 GPa, =0.9 MN/m, and = 1.2 . According to (13), (15), and (16) and the method introduced in Section 5, after a couple of trial calculations, the maximum support pressure of coal seam was found to be accurate to the sixth decimal place: Equations (84) and (85) show that as the hanging roof distance of goaf increases, the maximum support pressure of coal seam c3 increases, and the residual strength of coal seam at coal wall 3 ( ) decreases. When =24 m, the residual strength of coal seam 3 ( ) ≈0.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars have researched from different aspects to study the permeability and pore structure characteristics of the roof and floor strata in coal seams. Based on the nonlinear theory and stochastic differential equation, Miao et al [8][9][10][11][12][13][14] have studied permeability characteristics of cracked rock mass.…”
Section: Introductionmentioning
confidence: 99%